31st AIAA Applied Aerodynamics Conference 2013
DOI: 10.2514/6.2013-3155
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Flow Topology Around Several Airdrop Cargo Configurations at Static Conditions

Abstract: A numerical study was carried out to assess the interference effects between the wake of a transport aircraft and several generic cargo bodies during the early stage of an airdrop scenario. DLR carried out extensive wind tunnel airdrop investigations between 2006 and 2012. Based on the experimental data and preceding numerical simulations distinct positions of the trajectory being subject to strong interference effects were statically reproduced. The flow field around the bodies was experimentally investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A so called "strong coupling" approach was applied, which means that the coupled equations are iteratively solved within every physical time step by repeatedly solving the involved disciplines CFD and RBD separately. This coupling routine has been validated and successfully applied to several generic test cases as well as store release and gust encounter scenarios as described in [12], [15], [16] and [17].…”
Section: Numerical Setupmentioning
confidence: 99%
“…A so called "strong coupling" approach was applied, which means that the coupled equations are iteratively solved within every physical time step by repeatedly solving the involved disciplines CFD and RBD separately. This coupling routine has been validated and successfully applied to several generic test cases as well as store release and gust encounter scenarios as described in [12], [15], [16] and [17].…”
Section: Numerical Setupmentioning
confidence: 99%
“…The impact of the turbulence in predicting the flow field encountered in airdrop simulations was examined in separate studies. 18,19 It was shown that the Spalart-Allmaras model revealed the best compromise with respect to accuracy, efficiency and robustness and was therefore used in TAU.…”
Section: Verification Of Airbornementioning
confidence: 99%
“…In contrast to the conclusions of the aforementioned research groups DLR has decided to stick with its Reynolds-averaged Navier-Stokes flow solver TAU to examine and predict the airdrop trajectories. Based on a vast experimental data base, including PIV flow field 15,16 and trajectory measurements, 17 the suitability of the DLR TAU code to predict the general flow field 18,19 as well as first trajectories 20 was successfully demonstrated. Based on these promising results DLR further matured its high-fidelity approach and currently is able to predict the motion of simplified 6-DOF, 7-DOF and 8-DOF cargo and cargo-parachute systems within the vortical wake of the aircraft.…”
Section: Introductionmentioning
confidence: 99%